Sustainable development in vocational education: foreign experience - Haiduk, Olha; Kalenskyi, Andrii (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
Background. To follow sustainable development principles during and after the Ukrainian war and post-war economic recovery demands coordinated action and a systematic reconstruction policy. Taking into account sustainable development principles, the Ukrainian government must take measures to lessen the negative impact on the environment and increase the positive impact on society's development. In view of this, the task arises of such an organization of the sphere of vocational education and training, which takes into account modern trends in the development of an economy focused on the preservation of natural resources with simultaneous observance of the UN concept of education for sustainable development. This indicates the need to introduce new, eco-oriented and energy-efficient technologies, the maintenance and functioning of which will be provided by highly skilled workers who are able to professionally act in accordance with the principles of sustainable development. For professional training, this means that both future workers and retired military personnel who want to change their profession need to acquire competencies that will enable them to include sustainable development factors in their professional activities and, if possible, organize their work accordingly after graduation for the ecological post-war restoration of the country. M e t h o d s . Theoretical (analysis, synthesis, interpretation, abstraction, generalization, analogy and comparison – for structuring and analyzing the impact of sustainable development on vocational education in Germany); comparative - to adapt the experience of Germany to the conditions of the domestic system of vocational education; generalization - to formulate the conclusions of the study. Results. The impact of sustainable development on professional education in Germany, which has overcome its path from environmental education in vocational training to vocational training for sustainable development, is considered. It has been found that currently in Ukraine, at the level of state program documents and recommendations for the implementation of the Sustainable Development Goals, one can only see intentions to implement them. In the Standards of Education and, in particular, vocational education, and until now, in the requirements for learning outcomes, in the lists and descriptions of key competencies by profession, there is no competence focused on sustainable development, but only environmental and energy-efficient competence, which, in our opinion, is much narrower in its meaning. ConclusIons. The development considered in the article from environmental education to professional training for sustainable development in Germany shows that in order to better adapt education for sustainable development in vocational education in Ukraine, it is necessary to set the task of understanding the formation of competence focused on sustainable development in future skilled workers, taking into account the Sustainable Development Goals. To this end, it is necessary to intensify scientific research on the formation of the specified competence of future skilled workers with their subsequent introduction into the Standards of vocational education.
Keywords: sustainable development, education for sustainable development, vocational education, Germany, Ukraine